The ABC transporter ABCG36 is required for cadmium tolerance in rice. (17th August 2019) - Fu, Shan; Lu, Youshe; Zhang, Xiang; Yang, Guangzhe; Chao, Dong; Wang, Zhigang; Shi, Mingxing; Chen, Jiugeng; Chao, Dai-Yin; Li, Rongbai; Ma, Jian Feng; Xia, Jixing
Abstract : OsABCG36 localized at the plasma membrane functions as an efflux transporter for Cd or Cd conjugates in the roots, and is involved in Cd tolerance in rice. Abstract: Cadmium (Cd) is a highly toxic heavy metal in nature, which causes severe damage to plant growth. The molecular mechanisms for Cd detoxification are poorly understood. Here, we report that a G-type ATP-binding cassette transporter, OsABCG36, is involved in Cd tolerance in rice. OsABCG36 was expressed in both roots and shoots at a low level, but expression in the roots rather than the shoots was greatly up-regulated by a short exposure to Cd. A spatial expression analysis showed that Cd-induced expression of OsABCG36 was found in both the root tip and the mature root region. Transient expression of OsABCG36 in rice protoplast cells showed that it was localized to the plasma membrane. Immunostaining showed that OsABCG36 was localized in all root cells except the epidermal cells. Knockout of OsABCG36 resulted in increased Cd accumulation in root cell sap and enhanced Cd sensitivity, but did not affect tolerance to other metals including Al, Zn, Cu, and Pb. The concentration of Cd in the shoots was similar between the knockout lines and wild-type rice. Heterologous expression of OsABCG36 in yeast showed an efflux activity for Cd, but not for Zn. Taken together, our results indicate that OsABCG36 is not involved in Cd accumulation in the shoots, but is required for Cd tolerance by exporting Cd or Cd conjugates from the root cells in rice.